(untitled) (International Journal of Engineering and Computer Science, 2017)
Now a days because of vast and intelligent use of technology things are becoming extremely easy and user friendly. The pace in which development of technology had been done is certainly giving the way for invention of many amazing and revolutionary products which may help people in their day to day life. Robotics is one of such field which makes lives of people to surprising ease and comfort, so this field promises to be one of the most stalwart fields of engineering. With the development of high speed computers and because of which increasing their computational capacity have given us a way to think in a way to recognize gestures and make their use for other applications. So with combination of robotics and image processing we can make a robot move on the head movements by recognizing head gestures. Application of this can be done in field of human computer interaction and usability (HCIU) and create intelligent wheelchair (IW) that will move by recognizing the head movements done instead of traditional electronically powered wheelchairs that move on joysticks . So this paper presents a book of reference for hands free control of robot movement using head gesture recognition.